Flowering Phenology of Pinang Gajah (Nenga gajah J. Dransf.) in The Bogor Botanic Gardens - Rizmoon Nurul Zulkarnaen; Inggit Puji Astuti; Joko Ridho Witono; Aulia Hasan Widjaya; Harto Harto (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2022)
AbstractNenga gajah J. Dransf. is an endemic palm species originating from the island of Sumatra. The palm is one of the collections of the Bogor Botanic Gardens with seven collection numbers of N. gajah from Jambi and Riau. However, the reproduction information of the palm is still unknown until now. Information on the phenology of flowering is essential in conservation activities, especially its presence in nature and the production of seeds for reintroduction purposes. This study aims to determine the phases and timing of the flowering period and the factors that influence the flowering of N. gajah in the Bogor Botanic Gardens. This study was conducted on individuals at the phase of initiation of flowering. Flowering observation variables include the length of the period from flower buds to the anthesis phase until the flowers wither, and the fertilization process from young fruit to ripe. The flower and fruit of N. gajah were documented in each stage. The data recorded included flower and fruit development time for each phase and visiting insects. Data analysis was carried out descriptively to describe the process of flowering and fertilization that occurred. The results showed that the flower initiation phase took an average of 25.5 days, the anthesis phase took 6–7 days, the anthesis phase took 7–9 days, and the fruit formation and ripening phase took 100–120 days. Insects that are thought to act as pollinating insects for N. gajah include Trigona sp., Polyrachis sp., and Apis sp.AbstrakNenga gajah J. Dransf. merupakan salah satu jenis palem endemik yang berasal dari Pulau Sumatra. Palem tersebut menjadi salah satu koleksi Kebun Raya Bogor dengan tujuh nomor koleksi N. gajah yang berasal dari Jambi dan Riau namun informasi reproduksi palem tersebut masih belum diketahui hingga kini. Informasi fenologi pembungaan tersebut sangat diperlukan dalam kegiatan konservasi, khususnya keberadaannya di alam dan produksi biji untuk tujuan reintroduksi. Penelitian ini bertujuan untuk mengetahui fase-fase dan waktu periode pembungaan dan mengetahui faktor-faktor yang memengaruhi pembungaan N. gajah di Kebun Raya Bogor. Penelitian ini dilakukan terhadap individu yang berada pada tahap inisiasi pembungaan. Variabel pengamatan pembungaan meliputi panjang periode dari kuncup bunga menuju fase antesissampai bunga layu dan proses pembuahan dari buah muda sampai masak. Perkembangan bunga dan buah N. gajah didokumentasikan pada setiap fase, data yang dicatat meliputi waktu perkembangan bunga dan buah untuk setiap fase, serta serangga pengunjung. Analisis data dilakukan secara deskriptif untuk menggambarkan proses pembungaan dan pembuahan yang terjadi. Hasil pengamatan menunjukkan bahwa fase inisiasi bunga membutuhkan waktu rata-rata 25,5 hari, menuju fase antesis membutuhkan waktu 6–7 hari, fase antesis membutuhkan waktu 7–9 hari, dan fase pembentukan dan pematangan buah membutuhkan waktu 100–120 hari. Serangga yang diduga berperan sebagai serangga penyerbuk N. gajah antara lain Trigona sp., Polyrachis sp., dan Apis sp.